2016
DOI: 10.1213/ane.0000000000001197
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose or High-Dose Rocuronium Reversed with Neostigmine or Sugammadex for Cesarean Delivery Anesthesia: A Randomized Controlled Noninferiority Trial of Time to Tracheal Intubation and Extubation

Abstract: We conclude that rocuronium for rapid-sequence induction is noninferior for time to tracheal intubation and is accompanied by more frequent absence of laryngoscopy resistance and lower incidence of myalgia in comparison with succinylcholine for cesarean delivery under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Sugammadex was administered for antagonism in 28 studies (supplemental table S13, http://links.lww.com/ ALN/C928). Based on the available information (reported in the publication or obtained from authors), the train-offour ratio was confirmed greater than or equal to 0.9 before extubation in 10 studies, 60,62,68,73,86,118,139,142,179,180 greater than or equal to 0.8 or not stated in 2 studies, 128,191 and unconfirmed in 11 studies 59,63-66, 105,176,184,186,187,189 ; in 6 studies (1 had two strata), whether train-of-four ratio was confirmed could not be determined. 43,61,67,117,182,190 Copyright © 2022, the American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Sugammadex was administered for antagonism in 28 studies (supplemental table S13, http://links.lww.com/ ALN/C928). Based on the available information (reported in the publication or obtained from authors), the train-offour ratio was confirmed greater than or equal to 0.9 before extubation in 10 studies, 60,62,68,73,86,118,139,142,179,180 greater than or equal to 0.8 or not stated in 2 studies, 128,191 and unconfirmed in 11 studies 59,63-66, 105,176,184,186,187,189 ; in 6 studies (1 had two strata), whether train-of-four ratio was confirmed could not be determined. 43,61,67,117,182,190 Copyright © 2022, the American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 90%
“…The body of evidence enrolling adults included 191 studies (133 randomized controlled trials, 4,92,95,[98][99][100][101][102][103][104][110][111][112][113][114][118][119][120][121][122][123][124][125][126][127][132][133][134][135][136][137][138][139][140][141][145][146][147][148][155][156][157]163,[173][174][175][176][177][178][179][180][181] 11 nonrandomized trials, …”
Section: Antagonism Of Neuromuscular Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…Sugammadex, a cyclodextrin, can be used to reverse neuromuscular blockade induced with rocuronium or vecuronium in as little as two minutes 53. However, at this time it has not been studied in parturients though its use has been documented with no ill effect to mother or fetus54 but the ideal dose has yet to be established.…”
Section: Anesthetic Considerations For Cesarean Deliverymentioning
confidence: 99%
“…No difference in the Apgar score between the two groups was noticed. Less resistance during laryngoscopy and a lower incidence of postoperative myalgia were found in the group receiving rocuronium and sugammadex [28]. Since there is only little oral absorption, sugammadex can be administrated safely in breastfeeding women [10].…”
Section: Pregnant and Breastfeeding Womenmentioning
confidence: 99%